FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PRESTASI ANAK USIA SEKOLAH DI SD GMIM TUMPENGAN SEA DUA KECAMATAN PINELENG - Walansendow, Paulina I.M.; Mulyadi, Ns; Hamel, Rivelino (Universitas Sam Ratulangi, 2016)
Abstract: Education in general is very important school-age children for school age is considered as past or future intellectual. Aimof the study: .The purpose of this study to determine the level of achievement of school-age children in elementary GMIM Tumpengan Sea Village Pineleng Dua subdistrict.Methods:Design this study used cross sectional method. Samples: were taken from purposive sampling as many as 43 students. The instrument used in this study were questionnaires. Result: Research data obtained in the descriptive analysis presented in the form of tables and statistically for quantitative data using devices komputar and analysis using univeriat and bivariate analysis.Conclusion: Conclusion The achievement level of children of school age in the majority of primary school students GMIM Tumpengan Sea Village Two Pineleng District of achievement and has a physiological state, environmental and good instruments. Recommendations: Suggestions should be increased physiological conditions, environmental and instruments that have been either continuously, taking into account other factors that affect the level of achievement of school-age children, and invite parents to pay attention to children's education, especially at the time outside learning activities in schools by keeping kondidsi physiological children to stay fit. Keywords : Achievement of school-age children Abstrak:Pendidikan secara umum sangat penting terutama bagi anak usia sekolah karena masa usia sekolah di anggap sebagai masa intelektual atau masa keserasian bersekolah.Tujuan Penelitian: untuk mengetahui tingkat prestasi anak usia sekolah yang ada di SD GMIM Tumpengan Desa Sea Dua Kecamatan Pineleng.Metode: menggunakan metode Cross Sectional. Sampel di ambil dari purposive sampling yaitu sebanyak 43 siswa.Instrument yang digunakan dalam penelitian ini yaitu kuesioner.Hasil:data yang diperoleh di analisa secara deskriptif yang disajikan dalam bentuk table dan secara statistik untuk data kuantitatif dengan menggunakan perangkat komputar dan analisa dengan menggunakan analisa univeriat dan bivariat.Simpulan:tingkat prestasi anak usia sekolah di sebagian besar siswa SD GMIM Tumpengan Desa Sea Dua Kecamatan Pineleng berprestasi dan memiliki kondisi fisiologis, lingkungan dan intrumen yang baik.Saran: perlu ditingkatkan kondisi fisiologis, lingkungan dan intrumen yang sudah baik secara kontinyu, dengan memperhatikan faktor-faktor lain yang mempengaruhi tingkat prestasi anak usia sekolah, dan mengajak orang tua untuk memperhatikan pendidikan anak terutama pada saat di luar kegiatan belajar di sekolah dengan menjaga kondidsi fisiologis anak agar tetap prima. Kata Kunci : Prestasi anak usia sekolah